ANALISIS PEMBEBANAN TRANSFORMATOR GARDU SELATAN KAMPUS UNIVERSITAS TADULAKO - Rizky, Muhammad; Mukhlis, Baso; Adam, Ahmad Antares (MEKTRIK)
The unbalanced load in electric power distribution system always happen and it is caused by single phase loads on low voltage system. The effect of the unbalanced load is appear as a neutral current. These neutral current cause losses, those are losses caused by neutral current in neutral conductor on distribution transformers and losses caused by neutral current flows to ground. In conclusion, when high unbalanced load happened, then the neutral current that appear is also high.